Dynamics of Healing of Skin Cold Wounds, Lipid Peroxidation Level and Leucocyte Profile of Rat’s Blood Against the Background of Animal Extract Introduction - Shinder, A. V.; Galchenko, S. Ye.; Ostankova, L. V.; Synchykova, O. P. (Problems of Cryobiology and Cryomedicine, 2009)
There was examined the effect of the extract of cryopreserved fragments of porcine spleen (PSE) and the one of dead bee bodies (DBBE) on the dynamics of healing of skin cold wounds, LPO level and the blood indices of Wistar and Sphynx rats. It has been established that healing of cold wounds in Sphynx rats proceeds slower if compared with those for Wistar ones. The introduction of PSE and DBBE accelerates the healing of wounds, normalizes blood counts and reduces the level of lipid peroxidation. Porcine spleen extract has higher biological activity versus the bee’s extract.